Getting Started in Internal Social Responsibility: Evaluation of Integration between Social Accounting Audit and Internal Corporate Social Responsibility: Review of Literature - Satirenjit Kaur Johl , Fasilat Aramide Sanusi , Akanbi Taibat (International Journal of Advanced Science and Technology, 2020)
Social accounting and audit and internal corporate social responsibility are similar conceptsthat share equal value within the sphere of social activities. However, a comprehensive reviewthat portray understanding of academic concept alongside other non-academic event thatinfluence social expectations with respect to employee as an internal stakeholder is missing inthe existing studies. The purpose of this paper is to examine social integration that exist betweensocial accounting and audit and internal corporate social responsibility by reviewing the mostrelevant information that have contributed to their understanding and definitions. It should benoted that the integration of the two concepts continue to be the subject to multiple perceptions.The analysis conducted shed light on the group of issues that emerged with regards to politics,economic and stakeholder’s interests which must be continuously explore in order to respond tosocial demand of employees with respect to job. Social accounting and audit and internalcorporate social responsibility is expected to remain part of organization’s sustainabledevelopment. Therefore, there is plausible future for social accounting and audit and internalcorporate social responsibility if considerable attention is given to their integrative approach